2013
DOI: 10.6061/clinics/2013(07)20
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training induces metabolic benefits in rats with metabolic syndrome independent of dietary changes

Abstract: OBJECTIVES:We evaluated the effects of aerobic exercise training without dietary changes on cardiovascular and metabolic variables and on the expression of glucose transporter Type 4 in rats with metabolic syndrome.METHODS:Twenty male spontaneously hypertensive rats received monosodium glutamate during the neonatal period. The animals were allocated to the following groups: MS (sedentary metabolic syndrome), MS-T (trained on a treadmill for 1 hour/day, 5 days/week for 10 weeks), H (sedentary spontaneously hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 40 publications
5
47
1
2
Order By: Relevance
“…For example, white fibers are less affected by aerobic activity in terms of GLUT4 and insulin sensitivity. However, the results of present study are consistent with the findings of Durant (2002) increase of GLUT4 transportation to cell membrane (Paula et al, 2002), Caponi et al (2013) increase of GLUT4 (Caponi et al, 2013), Park et al, (2011) increase of GLUT4 (Park et al, 2011), Zarekar et al (2014) increase of GLUT4 and insulin sensitivity (Zarekar et al, 2014), andCatherine et al, (2013) increase of GLUT4 and improved insulin sensitivity (Katharine et al, 2013). The GLUT4 protein is a major mediator for glucose uptake from blood circulation which is expressed in skeletal muscle and adipose tissue (Huang and Czech, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…For example, white fibers are less affected by aerobic activity in terms of GLUT4 and insulin sensitivity. However, the results of present study are consistent with the findings of Durant (2002) increase of GLUT4 transportation to cell membrane (Paula et al, 2002), Caponi et al (2013) increase of GLUT4 (Caponi et al, 2013), Park et al, (2011) increase of GLUT4 (Park et al, 2011), Zarekar et al (2014) increase of GLUT4 and insulin sensitivity (Zarekar et al, 2014), andCatherine et al, (2013) increase of GLUT4 and improved insulin sensitivity (Katharine et al, 2013). The GLUT4 protein is a major mediator for glucose uptake from blood circulation which is expressed in skeletal muscle and adipose tissue (Huang and Czech, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies [31,32] showed that low-to-moderate PT intensity is effective in inducing benefits by preventing the establishment of MS. In these studies [31,32] PT began with the start of the diet for development of MS. Few studies [1,18] have evaluated PT as a treatment of already established MS. These studies show that PT induces a reduction in systolic blood pressure, together with increased sensitivity to insulin and in the gene expression of GLUT4 in white adipose tissue and gastrocnemius muscle [1], and reduces retroperitoneal and epididymal fat [18,33].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies [31,32] PT began with the start of the diet for development of MS. Few studies [1,18] have evaluated PT as a treatment of already established MS. These studies show that PT induces a reduction in systolic blood pressure, together with increased sensitivity to insulin and in the gene expression of GLUT4 in white adipose tissue and gastrocnemius muscle [1], and reduces retroperitoneal and epididymal fat [18,33]. In our present study, PT should be considered a treatment because it started in the last 6 weeks of the diets, and therefore with an already established MS disorder, as shown through the increased MAP, HR and body mass of the rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations